Evaluation of Water Use Efficiency Algorithms for Flux Variance Similarity‐Based Evapotranspiration Partitioning in C3 and C4 Grain Crops. Issue 5 (7th May 2021) - Wagle, Pradeep; Skaggs, Todd H.; Gowda, Prasanna H.; Northup, Brian K.; Neel, James P. S.; Anderson, Ray G.
Abstract: Despite the high sensitivity of Flux Variance Similarity (FVS) partitioning to leaf‐level water use efficiency (WUE), relatively little work has been done comparing WUE algorithms. We evaluated four intercellular CO2 concentration parameterizations (constant_ppm, constant_ratio, and linear and square root functions of vapor pressure deficit) and one optimized WUE approach using eddy covariance data for three C3 (wheat – Triticum aestivum L., canola – Brassica napus L., and soybean – Glycine max L.) and two C4 (maize – Zea mays L. and sorghum – Sorghum bicolor L. Moench) grain crops. The different data requirements of the WUE models resulted in discrepancies in the number of partitioned outputs among WUE algorithms. The transpiration:evapotranspiration (T:ET) ratios found with the five WUE algorithms varied by 6%–8% for soybean and maize, 12%–13% for wheat and canola, and 22% for sorghum. The crops producing larger variations in computed T:ET also tended to have higher estimated WUE magnitudes. The constant_ppm and constant_ratio parameterizations showed better potential to partition ET in all crops, except soybean. The linear and square root WUE models failed to produce reduced T:ET ratios during wet periods in all crops, except soybean. The optimized WUE approach has potential as a benchmark for comparing other WUE algorithms for C3 crops. The applicability of the linear and optimized WUE approaches was uncertain in C4 crops. Agreement and disagreement among the five WUE algorithms in multiple crops provide new perspectives for applying FVS partitioning to a range of biomes and climate conditions. Key Points: Flux Variance Similarity (FVS) partitioning shows high sensitivity to water use efficiency (WUE) estimates from five WUE algorithms Five WUE algorithms yielded considerable differences in FVS algorithm performance and partitioned transpiration:evapotranspiration ratios Optimized WUE approach showed the potential to use as a benchmark to compare with other WUE algorithms for sensitivity analysis in C3 crops